Anticonvulsant vs. Proconvulsant Effect of in situ Deep Brain Stimulation at the Epileptogenic Focus - Chou, Ping; Kuo, Chung-Chin (Frontiers in Systems Neuroscience, 2021)
Because deep brain stimulation at the epileptogenic focus (in-situ DBS) denotes long-term repetitive stimulation of the potentially epileptogenic structures such as amygdala, hippocampus, and cerebral cortex, a kindling effect and aggravation of seizures may happen and complicate the clinical condition. It is thus highly desirable to work out a protocol with an evident quenching (anticonvulsant) effect but free of concomitant proconvulsant side effect. We found that in the basolateral amygdala (BLA), an extremely wide range of pulsatile stimulation protocols eventually leads to kindling effect. Only protocols with a pulse frequency ≤ 1 Hz or a direct current (DC), with all of the other parameters unchanged, could never kindle the animal. On the other hand, the aforementioned DC stimulation, even a pulse as short as 10 sec given 5 min before the kindling stimuli or a pulse given even to the contralateral BLA, is very effective against epileptogenicity and ictogenicity. Behavioral, electrophysiological, and histological findings consistently demonstrate success in seizure quenching or suppression as well as safety of the specific DBS protocol (e.g. no apparent brain damage by repeated sessions of stimulation applied to the BLA for 1 month). We conclude that in-situ DCS, with a novel and rational design of the stimulation protocol composed of a very low (~3% or 10 sec/5 min) duty cycle and assuredly devoid of the potential of kindling, may make a successful antiepileptic therapy with adequate safety in terms of little epileptogenic adverse events and tissue damage.